Dukungan Keluarga terhadap Kepatuhan Obat pada Pasien Human Immunodeficiency Virus dengan Harga Diri Rendah - Buntar Handayani; Sri Atun Wahyuningsih (Jurnal Keperawatan Silampari, 2020)
The purpose of the study was to determine the effect of family support in drug adherence on the subject of Human Immunodeficiency Virus with low self-esteem in the PELNI hospital in Jakarta. The research method in this study is Pre Experimental with One Group Pre-Test-Post Test Design. The results showed that family support could have a positive impact on reducing mental disorders in PLWHA, such as anxiety, stress, depression, and low self-esteem. Conclusions, the results of subjects I and II who experience low self-esteem cause disruption of self-role, disability, helplessness, negative self-ideal, and negative self-esteem. Keywords: Family Support, Low Self-Esteem, Medication Adherence, Human Immunodeficiency Virus